Recent Advances in the Allergic Cross-Reactivity between Fungi and Foods. (7th October 2022) - Xing, Haiyan; Wang, Jianyong; Sun, Yuemei; Wang, Hongtian
Abstract : Airborne fungi are one of the most ubiquitous kinds of inhalant allergens which can result in allergic diseases. Fungi tend to grow in warm and humid environments with regional and seasonal variations. Their nomenclature and taxonomy are related to the sensitization of immunoglobulin E (IgE). Allergic cross-reactivity among different fungal species appears to be widely existing. Fungus-related foods, such as edible mushrooms, mycoprotein, and fermented foods by fungi, can often induce to fungus food allergy syndrome (FFAS) by allergic cross-reactivity with airborne fungi. FFAS may involve one or more target organs, including the oral mucosa, the skin, the gastrointestinal and respiratory tracts, and the cardiovascular system, with various allergic symptoms ranging from oral allergy syndrome (OAS) to severe anaphylaxis. This article reviews the current knowledge on the field of allergic cross-reactivity between fungal allergens and related foods, as well as the diagnosis and treatment on FFAS.